The Simple Correlation and Path Coefficient Analysis for Yield and Some Yield Components of Durum Wheat in Two Seasons in Iraqi Kurdistan. - Tawfiq, Sherwan I.; Abdulqader, Shang H.; Abdulkhaleq, Dana A.; Hama, Shara J. (Sulaimani Journal for Pure and Applied Sciences, 2016)
This investigation was conducted during the winter seasons of 2012-2013 and 2013-2014 at Qlyasan Agriculture Research Station, Faculty of Agricultural sciences, University of Sulaimani, using split plot design the main plots conducted in Randomized Completely Block Design (RCBD) with three replicates to study the effect of organic matter and removal treatments on the yield of durum wheat Ovanto cultivars. Highly significant and positive correlations recorded between grain yield & spike weight, grain weight/spike and harvest index at the first season. At the second season highly significant and positive correlation were recorded between grain yield and spike weight and harvest index and significant and positive correlation with spike length and biological yield at the second season. Concerning the path coefficient analysis, grain yield represented the dependent variable and no. of spikes/m2, spike weight/m2, average spike length, no. of spikelets/spike, no. of grains/spike, grains weight/spike,1000-grain weight, biological yield (t/ha) , harvest index and grain yield (t/ha), were the independent ones. Maximum and positive direct effect in grain yield recorded by grain weight/spike at the first season and harvest index at the second season reaching 0.639 and 0.822 respectively.
Keywords: Durum wheat; Yield,Correlation coefficientand path analysis